Instrumentation for safe vehicular flow in intelligent traffic control systems using wireless networks - Eren, Halit; Pakka, Hariani; Alghamdi, Ahmed; Yue, Yizuo (IEEE, 2013)
This paper describes a ZigBee based wireless system to assists traffic flow on arterial urban roads. Real-time simulation in laboratory environment is conducted to determine the traffic throughput to avoid possible congestions or ease existing congestions. Random numbers are generated to mimic approaching traffic, and this information is shared by a ZigBeebased real-time wirelessly network. Wireless nodes are connected to different PLCs representing different traffic lights in a cluster. Once the information is shared the timing and sequencing decisions are taken collectively in a synchronized manner. In this paper, the information is displayed on SCADA connected to each PLC for viewing the characteristics of continuous vehicular flow. It is found that the topology of the network can play an important role in the throughput of data, which may be critical in safety critical operations such as the control of traffic lights. This paper aims to highlight some of the possible effects of dataflow flow and time-delays faced by modern intelligent control of traffic lights.